A Model for Program Improvement Using Reflections by EdD Scholars About Adaptation During a Pandemic Time - Jacqueline Hawkins; Monica Martens (Impacting Education, 2024)
The results of a reflective survey, used for program evaluation, demonstrate how EdD scholars used their learning about Improvement Science as an insightful lifeline and for practical guidance within their professional practice in an uncertain time. Scholars imparted valuable information to EdD faculty about the strains and challenges they were under. Faculty, in turn, enhanced their choice of content and approaches to teaching about how to manage actionable change and becoming a more reflective and resilient practitioner. In CPED-influenced programs such as ours, this exchange of learning is ongoing and natural, as scholars pitch up problems of practice in need of immediate progress and improvement—sharing insights into strategies (successful or failed)—with faculty. Program learning and enhancements, in light of our students' lived experience and learnings, are discussed. We conclude with guidance about tools and procedures to navigate turbulence in educational systems.